Working from Home During the COVID-19 Pandemic: Lessons on Well-Being, Work-Life Balance, and Health - Valentina Franca; Polona Domadenik Muren (Sosyal Siyaset Konferansları Dergisi)
Increased levels of work from home, the most significant pandemic legacy, is here to stay, necessitating its examination from different perspectives. This paper focuses on the well-being, work-life balance and health challenges this paradigm shift brings. In our survey of 241 Slovenian companies, we found that the experience of forced work from home was better than expected, though it still poses risk to well-being, work-life balance and health, and that consensual work from home positively influences worker satisfaction, leading to increased productivity. However, the forced work from home resulting from the COVID-19 pandemic is not comparable to consensual remote work because it provides a more controlled environment; it is, therefore, critical that workers and their representatives are involved in organizing work from home with management to develop strategies to better develop motivation and optimize productivity. Further research should focus on longitudinal studies to specifically examine the impact on workers in this context, which will also provide a more robust basis for formulating recommendations and policy.